ОСОБЛИВОСТІ ІНТЕГРАЦІЇ СИСТЕМ ПОСТІЙНОГО СТРУМУ В МАГІСТРАЛЬНІ МЕРЕЖІ ЗМІННОЇ НАПРУГИ - Білик, А.В. (Інститут електродинаміки Національної академії наук України, 2017)
Investigated aspects of DC systems composed of alternating voltage grids. Studied issue of harmonics in systems of high voltage direct current (HVDC). Analyzed and studied the causes of harmonic components in the output voltage of HVDC converters. Describe the conditions and methods to reduce the harmonic spectrum. Investigated the model of hybrid power AC and DC. As a result of simulations experimentally, removed characteristics of current and its harmonic spectrum magnetization under different conditions. References 3, figures 3.